Improved methods for color image demosaicking - Zhu, Liyu. (2008)
Digital still color cameras sample the visible spectrum using an array of color filters overlaid on a CCD such that each pixel samples only one color band. The resulting mosaic of color samples is processed to produce a high resolution color image such that a value of a color band not sampled at a certain location is estimated from its neighbors. This process is often referred to as "demosaicking".